2000
DOI: 10.1021/jp000124y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of SiC Nanowires through a Reduction−Carburization Route

Abstract: Cubic silicon carbide (3C-SiC) nanowires were synthesized through a reduction-carburization route by using silicon powders and tetrachloride (CCl 4 ) as Si and C sources, and metallic Na as the reductant at 700 °C. The as-prepared SiC nanowires were characterized and studied by X-ray powder diffraction, transmission electron microscopy, X-ray photoelectron spectra, Raman backscattering, and photoluminescence spectra at room temperature. The SiC nanowires produced from the present route typically have diameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(88 citation statements)
references
References 30 publications
6
78
3
1
Order By: Relevance
“…It is clearly observed that a strong emission peak centered at about 403 nm. Compared with the previously reported PL spectra of the 3C-SiC nanowires [22] or films [23], the emission peak for the 3C-SiC product is obviously blue shifted. Recently, various emission wavelengths from 3C-SiC nanostructures have been reported [22,24,25], suggesting that the luminescence characteristics depend strongly on the dif- ferent SiC nanostructures (usually obtained via different synthesis conditions).…”
Section: Resultscontrasting
confidence: 85%
“…It is clearly observed that a strong emission peak centered at about 403 nm. Compared with the previously reported PL spectra of the 3C-SiC nanowires [22] or films [23], the emission peak for the 3C-SiC product is obviously blue shifted. Recently, various emission wavelengths from 3C-SiC nanostructures have been reported [22,24,25], suggesting that the luminescence characteristics depend strongly on the dif- ferent SiC nanostructures (usually obtained via different synthesis conditions).…”
Section: Resultscontrasting
confidence: 85%
“…2c is the deconvolution of the Si2p peaks and it demonstrate the percentage of silicon containing compounds. The peaks at 101.09, 103.14 and 99.56 eV correspond to Si-C [38], SiAO [39] and Si-Fe 3 [40], respectively. The trace Fe 3 -Si stem from the tip of the nanowires, which is agreement with the XRD analysis.…”
Section: Characterization Of Sic Nws -Gss Hybrid Nanofillersmentioning
confidence: 99%
“…Room temperature photoluminescence (RTPL) observations have been reported in a number of experimental works dealing mainly with the growth of SiC NWs and figure 15 shows various RTPL spectra recorded from SiC NWs [6,53,55]. In most cases a broad band peak between 430 and 460 nm is present showing a blue-shift in comparison to the RTPL of bulk and/or thin film 3C-SiC exhibiting a near band-edge peak at 540 nm associated with nitrogen doping [56].…”
Section: Photoluminescencementioning
confidence: 99%